PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP KINEJA PEGAWAI NEGERI SIPIL DI KANTOR KECAMATAN MAPANGET KOTA MANADO - KAFAU, JUBAIR; POSUMAH, JOHNNY HANNY; MAMBO, RULLY (Sam Ratulangi University, 2016)
Abstract : This research is funded on the basis of initial observations based on data on Office kecematanmapanget, found still lack of employee training in the following technical-related jobs, the impact of that lead tomost employees less active in carrying out his work.The method in use in the research is descriptive-quantitative methods with the population and sample as many as21 people, and the data collection technique using three research instruments namely interview techniques,questionnaire, and observations Division. In addition to the instruments of these three researchers also conductstudies libraries by way of quoting opinion opinion expert severely bekaitan directly with the research andsubsequent variable in the analysis using statistic infrensial i.e. regression analysis and correlation analysis ofsimple liner is simpleBased on the results of data analysis, note that: a descriptive analysis results through technical analysis table(table frequency) Note that the distribution of the answers of the respondents against variable training andeducation (training) are on the category of